Economic Recession as a Correlate of Teacher Productivity in Kwara State Secondary Schools, Nigeria - Tijani,, A. A.; Abdullahi,, N. J. K. (Kashere Journal of Education, 2021)
The study examined the relationship between current economic recession in Nigeria and teacher productivity in Kwara State. Descriptive research design of correlation type was adopted for the study. The target population comprised all teachers in the 304 public secondary schools in the state. 20 secondary schools were selected using stratified random sampling technique. 400 respondents were chosen through simple random sampling method. The instrument tagged “Economic Recession and Teacher Productivity Questionnaire” (ERTPQ) was designed to elicit information from the respondents. The two research questions raised were answered using descriptive statistics. The three generated hypotheses were tested using inferential statistics. The finding of the study revealed that current economic recession has brought about a low level of teacher job performance in recent times. Also, there were a positive and high significant relationship between Economic Recession, Inflation, Cost of living and teacher productivity. Hence, economic recession was a great determinants of teacher productivity in Kwara State Secondary Schools, Nigeria. The study thus recommends that government should put necessary monetary and fiscal policies in place to reduce the cost of livings. Also, there is urgent need for the upward review of minimum wages from the present meagre amount of N18, 000 per month.